Single nucleotide variants of filaggrin and glucocorticoid receptors genes in children suffering different phenotypes of atopic diseases - Dityatkovsky , V.O.; Naumenko , N.V.; Alifirenko, О.O.; Pinaeva , N.L.; Taran , S.T.; Filatova, I.A.; Abaturov , O.Ye. (Medicni Perspektivi, 2022)
Currently, there is an apparent need for genotype-associated personalization of the diagnostic process for atopic diseases (AtD) in children: atopic dermatitis (AD), seasonal allergic rhinitis (conjunctivitis – (SAR(C)), perennial allergic rhinitis (conjunctivitis – (PAR(C)) and bronchial asthma (BA) in different phenotype combinations - monotopic and polytopic. The aim of the study was to identify associations of the genotype variants of SNV rs_7927894 of FLG gene, rs10052957 and rs41423247 of NR3C1 gene in children with AD, SAR(C), PAR(C) and/or BA in mono- and polytopic phenotypes. The study recruited 293 children with AD who were divided into 6 phenotypic clusters: monotopic phenotypes: No. 1 – AD (58 patients); No. 2 – SAR(C)/PAR(C) (71 patients); No. 3 – BA (23 patients); polytopic phenotypes: No. 4 – AD+ SAR(C)/PAR(C) (43 patients), No. 5 – BA+SAR(C)/PAR(C) (72 patients), No. 6-AD+BA+SAR(C)+PAR(C) (26 patients). In patients of all 6 clusters buccal swab of the oral mucosa was taken for genotyping the variants: C/C, C/T, T/T SNV rs7927894 of FLG gene; A/A, A/G, G/G SNV rs10052957 and C/C, C/G, G/G SNV rs41423247 of NR3C1 gene. Heterozygous variant C/T SNV rs_7927894 FLG is the most common, directly associated and significantly increases the risk of polytopic AtD phenotypes: AD+SAR(C)/PAR(C) by 2.47 (95% CI 1.14-5.38, p<0.05) times and AD+BA+SAR(C)+PAR(C) – by 3.13 times (95% CI 1.24-7.95, p<0.05) related to monotopic phenotype SAR(C)/PAR(C). The heterozygous variant A/G SNV rs10052957 of the NR3C1 gene is the most common in all AtD phenotypes, except for monotopic BA and polytopic AD+SAR(C)/PAR(C), and significantly, by 0.40 times (95% CI 0.18-0.93, p<0.05) reduces the risk of the polytopic phenotype related to AD. Homozygous variant G/G SNV rs10052957 of the NR3C1 gene is most common in the monotopic phenotype SAR(C)/PAR(C) and polytopic AD+SAR(C)/PAR(C) as well as in AD+BA+SAR(C)/PAR(C) and significantly increases by 2.97 times (95% CI 1.31-6.74, p<0.05) and decreases by 0.45 times (95% CI 0.21-0.97, p<0.05) the risk of developing AD+SAR(C)/PAR(C) related to AD. Heterozygous variant A/G rs10052957 of the NR3C1 gene significantly reduces by 0.40 times (95% CI 0.18-0.93, p<0.05) the risk of polytopic phenotype BA+SAR(C)+PAR(C) related to AD+SAR(C)/PAR(C). Heterozygous variant C/G SNV 41423247 of the NR3C1 gene was the most common and significantly increased by 2.03 times (95% CI 1.01-4.10, p<0.05) the risk of monotopic AD phenotype related to SAR(C)/PAR(C).